THE CRYSTAL CHEMISTRY OF SENKEVICHITE, CS K NA CA2 TI O [SI7O18(OH)], FROM THE DARA-I-PIOZ ALKALINE MASSIF, NORTHERN TAJIKISTAN - Uvarova Y.A.; Sokolova E.; Hawthorne F.C.; Agakhanov A.A.; Pautov L.A.; Karpenko V.Yu. (My University, 2006)
The crystal structure of senkevichite, ideally Cs K Na Ca2 Ti4+ O [Si7O18(OH)], triclinic, P1̄, a 10.4191(4), b 12.2408(5), c 7.0569(3) Å, α 90.857(1), β 99.193(1), γ 91.895(1)°, V 887.8(1) Å 3, Z = 2, Dcalc 3.125 g/cm3, from Dara-i-Pioz, Tien-Shan Mountains, Tajikistan, has been refined to R1 = 4.5% for 4872 unique (Fo > 4σF) reflections collected on a Bruker single-crystal P4 diffractometer equipped with a 4K CCD detector and MoKa X-radiation. Electron-microprobe analysis gave SiO2 51.08, TiO2 8.94, FeO 0.50, MnO 2.59, CaO 10.98, K2O 6.13, Na2O 3.76, Nb2O5 0.64, Cs2O 15.28, (H2O)calc 1.09, sum 100.99 wt.%, and (H2O) was determined from crystal-structure analysis. Senkevichite is isostructural with tinaksite and tokkoite. There are seven tetrahedrally coordinated Si sites with a grand distance of 1.623 Å. Six of these sites are coordinated by O atoms, and the Si(7) site is coordinated by three O atoms and one (OH) group, i.e., this is ah acid silicate group. There are three [6]-coordinated M sites. The M(1) site is occupied primarily by Ti4+ (with minor Nb) with <M(1)-O> = 1.985 Å. The M(2) site is occupied solely by Ca, with <M(2)-O> = 2.382 Å, and the M(3) site is occupied by Ca (with minor Fe2+ and Mn2+), with <M(3)-O> = 2.317 Å. There is one [7]-coordinatcd Na site with = 2.504 Å. There are two A sites, the [ 12]-coordinated A(1) site, occupied mainly by Cs (with minor K), with <A(1)-O> = 3.318 Å, and the [10]-coordinated A(2) site, occupied solely by K, with <A(2)-O> = 2.987 Å. Senkevichite is a Cs-analogue of tinaksite, K2 Na Ca2 Ti4+ O [Si7O18(OH)], anda Cs-Na-Ti4+ oxyanalogue of tokkoite, K2 Ca4 F [Si7O18(OH)].
Keywords: ACID SILICATE GROUP; CRYSTAL-STRUCTURE REFINEMENT; SENKEVICHITE; TINAKSITE; TOKKOITE